BANASPATI RAJA DALAM PENCIPTAAN SENI LUKIS KONTEMPORER - Sucipta, I Wayan Adi (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2023)
Banaspati Raja is a mythical creature in the teachings of Balinese Hinduism as a guardian to protect the forest. The figure of Banaspati Raja represented in the form of sacred barong ket is believed to be able to protect the public from danger. The values of the Banaspati Raja seemed to not be fully understood. This phenomenon can be seen from the deterioration of Bali`s natural condition from year to year. The phenomenon arousing a sense of creator to create contemporary painting to aware the mindset or behavior of the people who mistakenly. The main purpose of creation is to create painting of new visually as well as have high aesthetic value. The painting is created is expected to be useful as a means of education, information and documentation for the development of the visual art of Bali. The creation of artwork is based on Sartre`s aesthetic theory with regrard to imagination as the basis for creating beautiful painting. Combined with the creation visual art structures includes elements of visual art by considering its principles. The process of creating painting through three stages, namely: exploration, visual experiments and visualization. The process of creating artworks eventually produced contemporary painting with the title Banaspati Raja. The painting is imagine the myth and the philosophy of banaspati raja through the image or symbol of the barong ket, the trees, water and mountain. Contemporary values are reflected through various technical mixes including brush strokes, pallete knive, splashes, collage, sigar warna, cawi-an and aburan. The artworks created also combines two different media, namely cnvas with recycled paper. The use of recycled paper in addition to producing variations texture, at least able to tackle the paper waste in Bali.